2021
DOI: 10.1186/s12909-021-02698-5
|View full text |Cite
|
Sign up to set email alerts
|

Student and educator perspectives on virtual institutional introductory pharmacy practice experience (IPPE)

Abstract: Background The COVID-19 pandemic has required governments around the world to suspend face-to-face learning for school and university students. Colleges of pharmacy are faced with the challenge of training students in hospitals that are under considerable pressure at this time. The government of Saudi Arabia has moved all classes and training online to limit the spread of the virus. This study describes the experience of the Introductory and Advanced Pharmacy Practice Experience (IPPE and APPE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Compared to many other countries, Taiwan was more successful at controlling the spread of COVID; thus, in-hospital internships for pharmacy students did not undergo a complete shift to distance learning. However, the conditions in Taiwan were conducive to students transitioning to distance learning, considering that we found that 80.2% of the sample could easily find a space suitable for distance learning and 84% felt that Taiwan had sufficiently stable Internet speed to accommodate online distance learning; this was in contrast to Almohammed et al, who reported only 58.6% and 50.6% agreement, respectively [ 21 ]. Some students stated that the distance learning required an increased amount of attention and active participation; otherwise, the students felt, since there was no supervision of the distance learning, especially with closed cameras, that they might not achieve the same level of learning.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Compared to many other countries, Taiwan was more successful at controlling the spread of COVID; thus, in-hospital internships for pharmacy students did not undergo a complete shift to distance learning. However, the conditions in Taiwan were conducive to students transitioning to distance learning, considering that we found that 80.2% of the sample could easily find a space suitable for distance learning and 84% felt that Taiwan had sufficiently stable Internet speed to accommodate online distance learning; this was in contrast to Almohammed et al, who reported only 58.6% and 50.6% agreement, respectively [ 21 ]. Some students stated that the distance learning required an increased amount of attention and active participation; otherwise, the students felt, since there was no supervision of the distance learning, especially with closed cameras, that they might not achieve the same level of learning.…”
Section: Discussionmentioning
confidence: 71%
“…and ‘there were a lot of unnecessary assignments that took a lot of time, and it was inconvenient to carry out discussion with peers’. Almohammed et al stated that even with high-tech virtual-reality teaching tools, students still worried about practicing independently in the real world; since they were not prepared to communicate with patients in the real world, students were worried about their lack of practical experience [ 21 ]. Muflih et al found that more than 60% of pharmacy students believed that the barriers to distance learning included time-consuming courses [ 22 ], and the students in our sample also believed that extra time was needed to complete their distance-learning courses.…”
Section: Discussionmentioning
confidence: 99%
“…Medical students taking part in simulated management of common clinical scenarios unanimously agreed in a self-evaluation that simulation increased their clinical preparedness (Kasai et al, 2021). Similarly, 70% of pharmacy students agreed the bespoke simulated training course was bene cial to their future practice (Almohammed et al, 2021).…”
Section: Brewster Et Al 2021)mentioning
confidence: 98%
“…Overall, student experiences were positive and there was a high level of satisfaction with the materials presented. Most students felt that clear connections made between didactic knowledge and application of this knowledge within the training and that the virtual experiences helped them better understand relevance to pharmacy practice [26][27][28][29][30][31][32]. The collective data indicate that the most valuable aspects of the virtual APPE experiences were patient case presentations, journal clubs, topic discussions, and formal written assignments.…”
Section: Improvements and Innovations Within Experiential Education W...mentioning
confidence: 99%
“…In the study by Montepara et al, students noted that they appreciated working with a variety of preceptors from different specialties and practice settings within the same virtual APPE rotation experience [28]. Common student concerns included anxiety about a lack of adequate patient care experience, and many students noted that virtual APPE activities should not completely replace in-person APPE rotations [26,31]. Suggestions for improvement included standardizing how information is disseminated to multiple students for virtual presentations and the virtual platforms used [28].…”
Section: Improvements and Innovations Within Experiential Education W...mentioning
confidence: 99%